2019
DOI: 10.1149/2.0821913jes
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Dopamine and Uric Acid using Glassy Carbon Electrode Modified with Almond-Shell-Based Nanoporous Carbon

Abstract: Almond-shell-based charcoal was prepared by carbonizing almond shells under nitrogen atmosphere. Nanoporous carbon (NPC) was formed using the obtained activated charcoal by using potassium hydroxide. NPC exhibited a large surface area (1075 m 2 /g), narrow pore-size distribution (1-2 nm). NPC with Nafion was used to modify glassy carbon electrodes to prepare a highly-sensitive electrochemical sensor for simultaneous determination of dopamine (DA) and uric acid (UA) through differential pulse anodic stripping v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Baikeli et al [107] have reported the synthesis of BAC by heating almonds at 600°C combined with KOH activation for 2 h, which produces a material with a large surface area (1075 m 2 g À 1 ) and narrow pore-size distribution (1-2 nm) (Figure 12(a,b)). A GCE modified with the nanoporous BAC (NPC) employing nafion polymer can be used for the sensitive Farahi et al [108] used BAC synthesized by Hammani et al [102] to prepare BAC-CPE for trace level determination of dopamine.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baikeli et al [107] have reported the synthesis of BAC by heating almonds at 600°C combined with KOH activation for 2 h, which produces a material with a large surface area (1075 m 2 g À 1 ) and narrow pore-size distribution (1-2 nm) (Figure 12(a,b)). A GCE modified with the nanoporous BAC (NPC) employing nafion polymer can be used for the sensitive Farahi et al [108] used BAC synthesized by Hammani et al [102] to prepare BAC-CPE for trace level determination of dopamine.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Baikeli et al [107] . have reported the synthesis of BAC by heating almonds at 600 °C combined with KOH activation for 2 h, which produces a material with a large surface area (1075 m 2 g −1 ) and narrow pore‐size distribution (1–2 nm) (Figure 12(a,b)).…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…In recent years, as a member of the carbon family, BC, especially 3D-BC structures, has received increasing attention from researchers. Compared to other carbon-based electrode modification materials such as graphene and carbon nanotubes, BC is designed and obtained from natural biomaterials, which reduces the cost of sensor preparation and creates great economic [27,28,[37][38][39][40][41][42] The performance improvement diagrams of BC-based materials in b) DA, [16,24,[43][44][45][46][47][48][49] c) Pt 2+ , [38,41,[50][51][52][53][54][55][56] and d) H 2 O 2 [23][24][25]28,[57][58][59][60][61] in recent years. e) Comparison of the sensing performance of BC-based modified materials for DA, Pt 2+ , and AP.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon based materials have often played a very important role in the WE modification process as electrocatalysts, due to their biocompatibility, low toxicity, and high conductivity [11,18,[21][22][23][24]. The extraction of carbon materials from waste products has high potential, as it follows the green chemistry ideology of recycling and reusing the waste [25].…”
Section: Introductionmentioning
confidence: 99%